Effect the Information Processing Model According to the Error Scale to Learning and Accuracy the Performance of Blocking Skill of Volleyball For Juniors - Firas Kassop Rashd Dwayyeh; Muntadher Mohammed Ali; Mahmoud Nasser Radi Alkoofee (Indian Journal of Forensic Medicine & Toxicology, 2021)
Due to the special features of the volleyball game that differs from the rest of the games in the style of play as any mistake may lead to losing a point unlike the rest of the group games, and this requires the players to be well prepared in all skill, physical, technical and psychological aspects, these are closely related to the skillful performance of volleyball players, and as the barrier skill must be possessed by the volleyball player with the required level of accuracy, mastery and minimizing error to reach the best levels and learning this skill requires time and effort on the part of the coach and the player, so attention must be paid to the use of methods and auxiliary tools that contribute to enhancing the learning process of the juniors and are in line with the capabilities and capabilities of the players at this stage to accelerate the learning process and correct errors in early stages before becoming a method for the player in the advanced stages, the problem of the research is that most trainers identify errors in general and do not rely on scientific foundations and modern methods of learning and training, in addition to that the process of diagnosing errors by trainers does not use objectivity in judgment and error measures are one of the important scientific means in identifying errors clearly and in it some kind of Precision, in addition to the educational and training unit’s lack of multiple educational tools that contribute effectively to the educational and training units. In addition, the blocking wall skill is a very important skill that needs focus and attention in its learning for its mastery and accuracy, the aim of the research is to process the information and reduce the error rate according to measures of error in learning and accuracy of the performance of the wall skill in volleyball for juniors.